O modernismo singular de Sosígenes Costa - Malafaia, Jane de Paula (2007)
The objective of this study is to make better known the work of the poet Sosígenes Costa, in the hopes of expanding the research available on the diversity of his poetry. This research is based on the assumption that the poet transcends placement in the Modernist block of Twentieth Century Brazilian Literature. The modernism in Sosígenes Costa s poetry shows up as a means by which the poet expresses his vision of the world, gaining force within his work because it is the greatest literary movement of the 20th century. Nevertheless, it cannot be affirmed that Sosíneges Costa was a modernist without detriment to the other forms in which the poet manifests himself. It should be observed that his poetry contains a mixture of elements from the Parnasianismo , Symbolism, and Baroque, as in Sonetos Pavônicos, while simultaneously the very distinct free verse-style that stands out in his epic poem Iararana. Even though he fluctuates between different literary styles, the author demonstrates his resonance with some of the modernist practices, mainly through Anthropophagy and the use of intertextual resources such as parody and bricolage . The tangential nature of the poetry to Sosíge nes Costa in addition to his own delay in publishing his Obra Poética, contributed to the difficulty of his inclusion in the national literary panorama. For that reason, the work of Sosígenes Costa, after more than a century since the poet s birth, still awaits greater recognition.